2012
DOI: 10.1021/nl3026357
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Room-Temperature Photoluminescence in Triangular WS2 Monolayers

Abstract: Individual monolayers of metal dichalcogenides are atomically thin two-dimensional crystals with attractive physical properties different from those of their bulk counterparts. Here we describe the direct synthesis of WS2 monolayers with triangular morphologies and strong room-temperature photoluminescence (PL). The Raman response as well as the luminescence as a function of the number of S–W–S layers is also reported. The PL weakens with increasing number of layers due to a transition from direct band gap in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

194
1,394
8
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,487 publications
(1,603 citation statements)
references
References 46 publications
194
1,394
8
7
Order By: Relevance
“…6h). This suggests that the band gap of the edge region in liquid-exfoliated WS 2 is smaller than that of the centre, in agreement with previous results 56 . Most importantly, neither very small (B50 nm), nor reasonably sized (B300 nm) few-layer species show a notable PL signal further supporting that the nanosheets with a nominal AFM height of 3 nm are monolayered nanosheets.…”
Section: Resultssupporting
confidence: 93%
“…6h). This suggests that the band gap of the edge region in liquid-exfoliated WS 2 is smaller than that of the centre, in agreement with previous results 56 . Most importantly, neither very small (B50 nm), nor reasonably sized (B300 nm) few-layer species show a notable PL signal further supporting that the nanosheets with a nominal AFM height of 3 nm are monolayered nanosheets.…”
Section: Resultssupporting
confidence: 93%
“…For example, it has been reported that MoS 2 has emerged with a direct bandgap of 1.8 eV when reduced the thickness to monolayer 25. Because of this merit, Few layered 2DLMCs such as transition metal dichalcogenides (TMDs) (MoS 2 ,26, 27, 28 WS 2 ,29, 30, 31, 32, 33, 34, 35, 36 TiS 3 ,37 etc.) and group III–VI nanomaterials (InSe,38, 39, 40, 41, 42 GaSe,43, 44, 45, 46, 47, 48 etc.)…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The synthesis of these materials has been vastly improved over the last few years and many possible devices have been proposed and realised. [3][4][5][6] But to finally achieve their large-scale integration and production, it is necessary to make TMDs fully CMOS processable. One prerequisite for this is the deposition of subsequent layers on top of the TMD for gating and passivation as the performance and stability of TMD based devices hugely depends on their dielectric environment.…”
mentioning
confidence: 99%
“…8 The most common ALD process is the deposition of Al 2 O 3 from alternating exposures of trimethylaluminium (TMA, Al(CH 3 ) 3 ) and water according to the reaction: 9 2Al(CH 3 ) 3 …”
mentioning
confidence: 99%